Propaganda Against Islam On Social Media: A Systematic Literature Review - IMRAN, MUHAMMAD; AMEN, UME; NOOR, AMNA; RAHIM, RABIA (The journal of contemporary issues in business and government, 2021)
The main objective of the study to review the published literature on propaganda against Islam on social media. However, a detail review of literature has been conducted, in this regard, this study has reviewed the journals publications, websites, social media platforms such as Facebook, twitter, Instagram, WhatsApp. Anyhow, there are very few studies to do the systematic literature review on title of propaganda against Islam on social media, this is main source of motivation for current study. After careful review of literature, this study concluded that western media has portrayed the negative image of Muslims. Anyhow, we also have found that most of studies have conducted in western countries rather Muslims countries media. Some of studies also suggested that Muslims should use social media to answer and defend their point of view and give the clear and positive picture of Islam to non-Muslims. This study also proposes that Muslims should respond to any anti-Muslims post positively with constructive justification. Moreover, this is responsibility of Muslims countries to give the clear image of Islam to other world rather overlock the social media posts. Anyhow, this is literature-based study, the future study should conduct empirically. Besides, the future studies should compare the non-Muslim countries social media with Muslims countries social media to overcome the distance between these two communities.